France : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper analyzes France's fiscal stance using a structural stochastic model. The theoretical model features a forward-looking benevolent government that needs to decide the optimal fiscal stance given the level of public debt, the cyclical position of the economy, and expectations about future shocks. This paper shows that a fiscal consolidation can help build buffers that could help France confront the next downturn from a stronger fiscal position. The analysis highlights that, on average, fiscal policy in France exhibited a deficit bias over the past four decades, being unable to react to either rising debt levels, or cyclical conditions. A model-based analysis further confirms that fiscal policy was generally looser than warranted by cyclical and debt sustainability considerations, and this is only partly due to the fact policymakers need to take decisions based on real-time output gap measures that are subject to uncertainty.